KRITIK TEORETIS DAN REPOSISI AKAD WADIAH DALAM TABUNGAN DIGITAL SYARIAH: PERSPEKTIF FIQH MUAMALAH DAN MAQASHID SYARIAH DI ERA FINTECH - Siti Mutiah; Arbanur Rasyid (JSE: Jurnal Sharia Economica, 2026)
The implementation of wadiah contracts in digital sharia savings in Indonesia has undergone an essential shift from classical fiqh substance. Contracts that should be non-profit (tabarru') and aimed at safekeeping (yad amanah) have been modified into commercial instruments for collecting cheap funds (wadiah yad dhamanah). This research is a descriptive qualitative study, with direct interviews conducted at the institution. The results show that this shift is exacerbated by the issue of aggressively promoted bonuses, which blur the line between voluntary donations and promises of rewards that resemble usury. Digitalization accelerates this commercialization, reducing Sharia contracts to mere technical features without their ethical spirit. The ambiguity and unfairness of the benefits received by customers threaten the principles of hifz al-mal and hifz al-din. Without a fundamental repositioning, digital wadiah contracts risk losing their authenticity and turning Islamic banking into a mere replica of conventional banking with an Islamic label.